Sistem Manajemen Risiko Produksi Teh Hitam Pada Perusahaan Perkebunan Besar Negara - Heryanto, Mahra Arari; Pardian, Pandi; Aulia, Reza Melvina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Enterprise risk management system is an integrated approach in managing risks along production chain. Natural and market factors have a huge influence in risk management for agricultural processing production. House of Risk (HoR) method recognize various risk events and sources very well by considering the severity and occurrence of risk sources. However, this method cannot explain the relationships and connections between events and sources of their causes. This paper aims to complement the HoR method with a systems thinking approach so that relationships and connections between events and risk causes can be described in a system structure. The research results showed that various risk events and their causes are interconnected and continue to accumulate in two main sub-systems: the cultivation process sub-system and the processing process sub-system. These two sub-systems are connected by a company management sub-system which has control and influenced by risk events in the production process. Another finding is that financial risk is a systemic risk in the black tea production process.